2008
DOI: 10.1159/000126085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low Vision on Well-Being in 10 European Countries

Abstract: Background: Because of the growing life expectancy in developed countries and the exponential increase in vision loss with increasing age, a growing number of elderly persons will eventually suffer from visual impairment and blindness. This paper describes the association between self-reported vision and well-being in individuals aged 50 years and older and their families. Methods: Using binary logistic regressions on data from the 2004 Survey of Health, Ageing and Retirement in Europe (SHARE), we analysed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
64
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 58 publications
(44 reference statements)
6
64
0
Order By: Relevance
“…Several previous articles showed vision loss to be associated with a lower QOL, problems in performing daily activities such as driving and preparing meals, decreased mental and physical health, an increased risk of suicide as well as of death, and in some cases with a loss of independence [36]. Our results additionally demonstrate a strong impact of self-reported visual impairment on individual employment, and therefore on worker productivity and well-being.…”
Section: Discussionsupporting
confidence: 69%
“…Several previous articles showed vision loss to be associated with a lower QOL, problems in performing daily activities such as driving and preparing meals, decreased mental and physical health, an increased risk of suicide as well as of death, and in some cases with a loss of independence [36]. Our results additionally demonstrate a strong impact of self-reported visual impairment on individual employment, and therefore on worker productivity and well-being.…”
Section: Discussionsupporting
confidence: 69%
“…Although there is no established methodology of assessing mental well-being, the five quantitative mental well-being indicators used in this study are consistent with those of Monjon-Azzi and associates 24 and measure overall psychological well-being. Rather than studying each indicator individually, we used a latent variable in the SEM setting to create a more comprehensive composite measure of mental well-being.…”
Section: Discussionsupporting
confidence: 60%
“…Using 11 variables to capture emotional well-being from the population-based 2004 SHARE, MonjonAzzi and associates found a significant relationship between lower vision and well-being. 24 In a systematic review of 29 quantitative studies between 2001 and 2008, Nyman and coworkers 42 noted working-age adults with VI were significantly more likely to report lower levels of mental health, social functioning, and quality of life. With respect to wellbeing and mortality, Chida and Steptoe 23 performed metaanalysis of 35 studies in initial healthy populations and 35 studies of disease populations and documented positive psychological well-being has a favorable effect on survival in both healthy and diseased populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blindness and visual impairment are two important health issues, with economic and social implications for developed and developing countries (6). Studies have shown that visual impairment affects a person's quality of life and reduce social activities and independence (7,8).…”
mentioning
confidence: 99%